2019
DOI: 10.3400/avd.cr.19-00078
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of an Aortic Arch Aneurysm in a Patient with a Hypoplastic Left Vertebral Artery Terminating into the Posterior Inferior Cerebellar Artery

Abstract: We present a 76-year-old male with an aortic arch aneurysm and a hypoplastic left vertebral artery (VA). Endovascular repair with left subclavian artery (SCA) closure was planned. The right VA was dominant, while the left VA was hypoplastic, barely connected to the basilar artery, and appeared to terminate at the posterior inferior cerebellar artery (PICA). The VA sizes and flow patterns during ultrasonography confirmed these findings. Therefore, we performed endovascular repair with left SCA reconstruction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
2
3
Order By: Relevance
“…Sato et al reported that the diameter of the hypoplastic left VA was 2.8 mm and the diameter of the right VA was 4.2 mm, with a difference of 1.4mm. 12 In the present case, the hypoplastic V4 segment of the right VA was 1.67mm which was narrower than the diameter of the hypoplastic VA reported by Sato et al, albeit on the right side. 12 Sarah et al compared the PICA bilaterally between the genders(n=100), by using CT angiography.…”
Section: Vertebral Arterycontrasting
confidence: 66%
See 2 more Smart Citations
“…Sato et al reported that the diameter of the hypoplastic left VA was 2.8 mm and the diameter of the right VA was 4.2 mm, with a difference of 1.4mm. 12 In the present case, the hypoplastic V4 segment of the right VA was 1.67mm which was narrower than the diameter of the hypoplastic VA reported by Sato et al, albeit on the right side. 12 Sarah et al compared the PICA bilaterally between the genders(n=100), by using CT angiography.…”
Section: Vertebral Arterycontrasting
confidence: 66%
“…12 In the present case, the hypoplastic V4 segment of the right VA was 1.67mm which was narrower than the diameter of the hypoplastic VA reported by Sato et al, albeit on the right side. 12 Sarah et al compared the PICA bilaterally between the genders(n=100), by using CT angiography. They reported that the diameter of the right PICA ranged from 1.12 to 2.4mm and the diameter of the left PICA ranged from 1.13 to 2.37 mm.…”
Section: Vertebral Arterycontrasting
confidence: 66%
See 1 more Smart Citation
“…In the present study, the diameter of the right VA proximal to the origin of PICA was smaller compared to the corresponding part on the left side. Sato et al reported that the diameter of the hypoplastic left VA was 2.8 mm and the diameter of the right VA was 4.2 mm, with a difference of 1.4mm [33]. In the present case, the hypoplastic V4 segment of the right VA was 1.67mm which was narrower than the diameter of the hypoplastic VA reported by Sato et al, albeit on the right side [33].…”
Section: Vertebral Arterycontrasting
confidence: 66%
“…Chuang YM et al studied the MRI of 158 hemispheric ischemic stroke and 33 brainstem ischemic stroke cases and reported that the incidence of unilateral hypoplastic VA is 11.51%, with right-sided predominance [8]. Sato et al reported a hypoplastic left VA with the majority of the blood going from the left VA to the Left PICA despite the existing connections between the left VA and BA [33].…”
Section: Vertebral Arterymentioning
confidence: 99%